Bread and Other Edible Agents of Mental Disease - Bressan, Paola; Kramer, Peter (Frontiers in Human Neuroscience, 2016)
Perhaps because gastroenterology, immunology, toxicology, and the nutrition and agricultural sciences are outside of their competence and responsibility, psychologists and psychiatrists typically fail to appreciate the impact that food can have on their patients’ condition. Here we attempt to help correct this situation by reviewing, in non-technical, plain English, how cereal grains—the world’s most abundant food source—can affect human behavior and mental health. We present the implications for the psychological sciences of the findings that, in all of us, bread (1) makes the gut more permeable and can thus encourage the migration of food particles to sites where they are not expected, prompting the immune system to attack both these particles and brain-relevant substances that resemble them, and (2) releases opioid-like compounds, capable of causing mental derangement if they make it to the brain. A grain-free diet, although difficult to maintain (especially for those that need it the most), could improve the mental health of many and be a complete cure for others.